Axolotl : a first field guide to the amphibian that never grows up - Whited, Jessica LaMae, Dr (Young zoologist., 2024)
"Head into the wild to study axolotls in this field guide for kids. Join axolotl expert Dr. Jessica LaMae Whited as she explains how these cute amphibians can regrow their legs and why they never grow up! Filled with simple science and plenty of facts, it's a perfect book to inspire the next generation of zoologists." --